Power: Feminine Gender
The authors of this film, which resembles a TV collage, assert that matriarchy is the natural form of social organization in Ukraine, as women traditionally play a major role in villages, local government, and business. Unfortunately, the political history of the second half of the nineties - especially, election campaigns - leads us to a sad conclusion: "female" political projects are used by the ruling class to fake a semblance of European-style democracy and only serve to banish women to the periphery of political life. This film is part of the Gender Montage: Paradigms in Post Soviet Space film series. Nina Rudik, Vlad Gello